THE RELATION OF GREGORY AKINDYNOS TO BARLAAM THE CALABRIAN - ZACHARIOU, Andreas P. (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
In the writings of the fourteenth-century Hesychasts, Gregory Akindynos is characterized as a Barlaamite because his theological perceptions are considered to be no different from those of Barlaam the Calabrian. However, Akindynos himself rejects the designation of Barlaamite by denying that he is in agreement with Barlaam and claiming injustice and slander from the Palamite party. In order to support his contention, he draws attention to his strong opposition to Barlaam when the latter turned against the monks and their way of life. Nevertheless, his own writings contradict his assertion, since they testify to the identification of his theology with that of Barlaam.